2016
DOI: 10.1080/14647273.2016.1214755
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the long-term effects of single-dose methotrexate and salpingectomy on ovarian reserve in terms of anti-müllerian hormone levels

Abstract: The aim of this study was to compare the effects of single-dose methotrexate (MTX) and salpingectomy on ovarian reserve in women with ectopic pregnancy in the late post-treatment period. A total of 181 patients were included in the study; 56 of them received a single-dose of MTX, 45 of them had undergone salpingectomy treatment for ectopic pregnancy in the previous 12-18 months, and 80 healthy women constituted an age-matched control group. The anti-müllerian hormone (AMH), follicle stimulating hormone (FSH) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 35 publications
1
25
0
1
Order By: Relevance
“…Pooled analysis of group 1 studies ( n = 464) revealed no statistically significant change in serum AMH levels after salpingectomy (WMD −0.10 ng/mL; 95% CI −0.19 to 0.00, I 2 = 0%) with low heterogeneity between studies (Figure ) . Similarly, in group 2, overall analysis of two studies showed no statistically significant difference between the salpingectomy group ( n = 169) and control group ( n = 154) (WMD −0.11 ng/mL; 95% CI −0.37 to 0.14, I 2 = 77%) with high heterogeneity between studies (Figure ) .…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Pooled analysis of group 1 studies ( n = 464) revealed no statistically significant change in serum AMH levels after salpingectomy (WMD −0.10 ng/mL; 95% CI −0.19 to 0.00, I 2 = 0%) with low heterogeneity between studies (Figure ) . Similarly, in group 2, overall analysis of two studies showed no statistically significant difference between the salpingectomy group ( n = 169) and control group ( n = 154) (WMD −0.11 ng/mL; 95% CI −0.37 to 0.14, I 2 = 77%) with high heterogeneity between studies (Figure ) .…”
Section: Resultsmentioning
confidence: 98%
“…In group 1, pooled analysis of three studies including 96 participants aged <40 years revealed no statistically significant change in serum AMH level (WMD −0.05 ng/mL; 95% CI −0.47 to 0.57; I 2 = 0%) . In group 2 studies, all participants were aged <40 years and a sub‐analysis was therefore not performed .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations